2016
DOI: 10.1016/j.jag.2016.05.010
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive assessment of the correlations between field crop yields and commonly used MODIS products

Abstract: a b s t r a c tAn exploratory assessment was undertaken to determine the correlation strength and optimal timing of several commonly used Moderate Resolution Imaging Spectroradiometer (MODIS) composited imagery products against crop yields for 10 globally significant agricultural commodities. The crops analyzed included barley, canola, corn, cotton, potatoes, rice, sorghum, soybeans, sugarbeets, and wheat. The MODIS data investigated included the Normalized Difference Vegetation Index (NDVI), Fraction of Photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
56
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 39 publications
(36 reference statements)
6
56
2
Order By: Relevance
“…The correlation between yield and GCI/NDWI/NIR is between 0.72-0.74 from mid-July to mid-August, attributed to their high sensitivity to canopy green leaf volume, which directly contributes to grain growth. The negative correlations between NIR/VIs and yield (positive for the visible and SWIR bands) in April and May are consistent with previous studies (Johnson 2016) and related to the increasing trend of yield from low (earlier planting dates) to high latitudes (later planting dates). Heat stress variables, especially daytime LST, maximum and mean VPD, and maximum daily air temperature, have strong negative correlations with yield in summer consistent with previous findings (Lobell et al 2013).…”
Section: Yield Response To Climatic and Environmental Variablessupporting
confidence: 92%
“…The correlation between yield and GCI/NDWI/NIR is between 0.72-0.74 from mid-July to mid-August, attributed to their high sensitivity to canopy green leaf volume, which directly contributes to grain growth. The negative correlations between NIR/VIs and yield (positive for the visible and SWIR bands) in April and May are consistent with previous studies (Johnson 2016) and related to the increasing trend of yield from low (earlier planting dates) to high latitudes (later planting dates). Heat stress variables, especially daytime LST, maximum and mean VPD, and maximum daily air temperature, have strong negative correlations with yield in summer consistent with previous findings (Lobell et al 2013).…”
Section: Yield Response To Climatic and Environmental Variablessupporting
confidence: 92%
“…These results, in terms of both correlations and timing, are in line with Mahey et al [53]. Freeman et al [54] found NDVI and wheat grain yield to be highly correlated, establishing the potential to predict yield with remotely sensed data as reported subsequently in several studies for a variety of crop types [55][56][57][58].…”
Section: Yield and Ndvisupporting
confidence: 76%
“…Although negative correlations between NDVI and crop yield are reported in the literature for potato late in the season [55] and for canola, after bolting and once the plants start transitioning to the reproductive stages [59], there are few similar findings for cereal crops when analyzing single or multi cultivars [60][61][62][63]. All these latter authors found a negative correlation under severe stress conditions, such as high temperature and drought, during grain filling.…”
Section: Yield and Ndvimentioning
confidence: 99%
“…Knowing geographical distribution of given crops can help optimize available resources, when performing large scale ground observations (Song et al, 2017). For instance, early season crop masks are required to provide crop yield prediction and, consequently, crop production forecasting in the operational context which is important for food security (Becker-Reshef, Vermote, Lindeman, & Justice, 2010;Franch et al, 2015;Johnson, 2016;Kogan et al, 2013;López-Lozano et al, 2015;Shao, Campbell, Taff, & Zheng, 2015). Crop maps can be incorporated into the drought risk assessment models to quantify and map the risk at different scales (Skakun, Kussul, Shelestov, & Kussul, 2016a).…”
Section: Introductionmentioning
confidence: 99%